The influence of building project characteristics, quality of clients and design team attributes on green design performance measures adoption / Mohamed S. Abd. Elforgani - Abd. Elforgani, Mohamed S. (Institute of Graduate Studies, UiTM, 2012)
Increasing concern for environment has made building owners and designers to incorporate green design into their building projects. Buildings take about 40 per cent of energy consumption globally and have significant impact on the productivity and wellbeing of the occupants. However, the quality of design team attributes the quality of clients and the characteristics of the building projects have been argued to be the main factors that determine the green design performance of buildings. Therefore, the main objectives of this study are to measure the green design building performance, the quality of client and the attributes of the design team. This study also measures the extent to which the quality of design team attributes, the quality of clients and the characteristics of the building projects affect the green design performance of buildings.The study adopted a triangulation technique that combined both quantitative and qualitative methods of data collection.